Plantas de caf?? GM para resist??ncia a broca-do-caf??: avalia????o de biosseguran??a alimentar - Bezerra, Caroline de Andrade (2013)
Coffee is in international and Brazilian economical scenery as the second most important natural commodity. Despite that, coffee crops suffer great damage due to the coleopteran coffee borer (Hypothenemus hampei) attack leading to around US$ 500 million loss. In order to control the coffee borer, one strategy is the inhibition of the insect digestive enzyme ??-amylase by Phaseolus vulgaris amylase inhibitor 1 (??AI1). In this context, the research group of Plant-pest Molecular Interaction Laboratory developed GM coffee (Coffea arabica) plants expressing the P. vulgaris ??AI1 gene. This is a promising event to be used in coffee borer control by inhibiting starch insect digestion. However, releasing a GM crop for commercialization and human consumption is possible only after assessing food and environmental safety status, based on international and national procedures. This work is divided in two chapters. In the first chapter is presented the isolation of an amylase cDNA from H. hampei, designated AmyHha. The highest transcript levels of this amylase coincide with the feeding stages of insect, the second instar and adult stage. The Southern blot analysis showed the presence of only one copy of the AmyHha in the H. hampei genome. Finally, was carried out the construction of a structural model based on the AmyHha predicted protein sequence. In the second chapter, food safety of GM coffee crops expressing P. vulgaris ???-AI1 was evaluated. First, the evaluation of allergenic potential of GM coffee grains expressing ???-AI1 and the study of hemolytic effect and thermostability using coffee grains suggest absence of feeding risks concerning cytotoxic effects and inhibition of ???-AI1 after heat treatment. Otherwise, in vitro resistance to digestibility and in silico analysis suggest an allergenic risk of GM coffee grains due to ???-AI1 expression. Thus more investigation must be carried out in order to clarify allergenicity risks and in vivo consequences of this GM coffee grain consumption.